THE USE OF DRILLING METHOD IN INCREASING STUDENT’S GRAMMAR MASTERY AT VIII GRADE OF SMP WIDIATMIKA - Mira Suantari Ni Luh Putu; Sri Widiastuti Ida Ayu Made (Journal on Studies in English Language Teaching (JOSELT), 2021)
This research aimed to increase students’ grammar mastery by using drilling method in online learning at VIII.1 Grade of SMP Widiatmika in academic year 2020/2021. The subject of this research was students at VIII.1 grade of SMP Widiatmika that consisted of twenty-five students. This research was classroom action research which was conducted in two cycles based on Kemmis and McTaggart model. The data of this research were obtained by using the result of pre-test and post-test, and also item of questionnaire. The result of this research showed that there were increase in students’ grammar mastery after implementing the drilling method. Thus, the students also found that drilling method in this research was useful and effective to increase students’ grammar mastery.